The Effect of Delay on the Implementation Cost: Case Study on The West Java Government Office Building Project - Brapisko Aldici Fauzan; Dewi Yustiarini (JIPTEK: Jurnal Ilmiah Pendidikan Teknik dan Kejuruan, 2022)
The delay of work in the project will affect the duration and cost of project implementation. So far, the effect of delays on project implementation costs has not been applied in project control. The majority of project control is only carried out with the S curve of the project cost weights, which only observes the costs that have been implemented in the project but cannot observe the effect of the implementation and delay of work activity on the cost of project implementation. This study, Tracking Progress on the Microsoft project on the duration of work every week from the first week to the last week on the West Java Government Office Building Construction Project. Simulation tracking will show the increase or decrease in costs due to a project activity. Simulation Tracking on the West Java Government Office Building Project, there is a difference in the total duration of time, which has changed from 49 days to 88 days with a difference of 39 days, while for the planned project implementation costs of Rp.11,017,969,680-, it becomes Rp.11,368,005,964-,.